Symmetry breaking in syntax and the lexicon - Bauke, Leah S. (Linguistik Aktuell/Linguistics Today ;, 2014)
This book is a research monograph that explores the implications of the strongest minimalist thesis from an antisymmetric perspective. Three empirical domains are investigated: nominal root compounds in German and English, nominal gerunds in English and their German counterparts, and small clauses in Russian and English. A point of symmetry that has the potential of stalling the derivation emerges in the derivation of all of these constructions. Building on certain assumptions on how Merge works, this book shows that the points of symmetry can all be resolved in the same way; despite the fact.